Gasification of ‘Loose’ Groundnut Shells in a Throathless Downdraft Gasifier - Aondoyila Kuhe; Samuel Jacob Aliyu (Center of Biomass & Renewable Energy (CBIORE), 2015)
In this paper, gasification potential of biomass residue was investigated using a laboratory scale throatless downdraft gasifier. Experimental results of groundnut shell was gasified in the throatless downdraft gasifier to produce a clean gas with a calorific value of around 5.92 MJ/Nm3 and a combustible fraction of 45% v/v. Low moisture (8.6%) and ash content (3.19%) are the main advantages of groundnut shells for gasification. It is suggested that gasification of shell waste products is a clean energy alternative to fossil fuels. The product gas can be used efficiently for heating and possible usage in internal combustion engines.